Design Issues in Transgender Studies. (15th August 2016) - Hughes, James P.; Emel, Lynda; Hanscom, Brett; Zangeneh, Sahar
Abstract : Abstract: Transgender individuals constitute an important focus for HIV prevention, but studies in this population present some unique methodologic and operational challenges. We consider issues related to sampling, sample size, number of sites, and trial cost. We discuss relevant design issues for evaluating interventions in both HIV-negative and HIV-infected transgender populations, as well as a method for assessing the impact of an intervention on population HIV incidence. We find that HIV-endpoint studies of transgender individuals will likely require fewer participants but more sites and have higher operational costs than HIV prevention trials in other populations. Because any intervention targeted to transgender individuals will likely include antiretroviral drugs, small scale studies looking at potential interactions between antiretroviral therapy and hormone therapy are recommended. Finally, assessing the impact of an intervention targeted to transgender individuals will require better information on the contribution of such individuals to the population HIV incidence.